Entropy Measures Can Add Novel Information to Reveal How Runners' Heart Rate and Speed Are Regulated by Different Environments - Exel, Juliana; Mateus, Nuno; Gonçalves, Bruno; Abrantes, Catarina; Calleja-González, Julio; Sampaio, Jaime (Frontiers in Psychology, 2019)
Ecological psychology suggests performer-environment relationship as the appropriate scale for examining perception, action and cognition relationship. Developing performance requires variation in practice in order to design the attractor-fluctuation landscape. The present study aimed to identify the effects of variating environment levels of familiarity and sensorimotor stimuli, into regularity degree of speed, heart rate (HR) and short-memory in runners. Twelve amateur runners accomplished three 45-min running trials in their usual route, in unusual route, and athletics 400-m track, wearing GPS and a HR monitor. It was calculated sample entropy (SampEn) and complexity index (CI) over speed and HR. Pre and post-trial, participants performed the Backward Digit Span task for cognitive assessment. Higher entropies were found for the 400-m, compared to usual and unusual. Usual routes increased speed SampEn (63% of chances), but decreased HR CI when compared to unusual (60% of chances). Runners showed higher overall short-memory performance after unusual route, when compared to usual (85% of chances), indicating positive relation to attentional control. The contexts of practice may contribute to change predictability from single to multiple timescales. Thus, by considering that time structuring issues can help diagnosing habituation of training routes, this study brings novel information to the long-term process of training.